1968
DOI: 10.1128/jb.95.4.1407-1414.1968
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Properties of Mucor pusillus Acid Protease

Abstract: The protease produced by Mucor pusillus was recovered from a wheat bran medium by treatment with ammonium sulfate, ethyl alcohol, gel filtration and ionexchange chromatography. The yield of the enzyme was 55 %. The overall increase in the specific activity of the protease was 34-fold. The purified protease was most active at pH 3.8 and 5.6 against hemoglobin and casein, respectively. Optimal hydrolysis of casein was observed at 55 C. The enzyme was stable from pH 3.0 to 6.0. Enzyme inactivated by metal ions wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
15
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 13 publications
6
15
0
Order By: Relevance
“…Our result is in concordance with those observed by Somkuti and Babel (1968). Purification of crude enzyme yielded a preparation that, upon gel filtration, ion‐exchange chromatography and electrophoresis analysis, appeared to be homogeneous.…”
Section: Resultssupporting
confidence: 94%
“…Our result is in concordance with those observed by Somkuti and Babel (1968). Purification of crude enzyme yielded a preparation that, upon gel filtration, ion‐exchange chromatography and electrophoresis analysis, appeared to be homogeneous.…”
Section: Resultssupporting
confidence: 94%
“…Similarly, the pH stability of the enzyme determined by measurement of the relative activity after incubation at various pH revealed that the enzyme was also found to be stable in pH 4, which leads to the confirmation that the purified enzyme is an acid protease. Similar results were observed in protease production by Saccharomyces lipolytica and Mucor pusillus (Tetsuji and Ogrydziak, 1983;Somkuti and Babel, 1968), which had the optimum pH for protease activity to be around 4. The activity declined with further increase or decrease in the pH.…”
Section: Influence Of Ph and Temperature On Protease Activity And Stasupporting
confidence: 81%
“…These two important characteristics of the proteases probably account partly for the wide ecological and geographical distribution of these fungi. The protease of Rhizomucorpusillus, was also optimally active at p H 5.4-5.6 when casein was used as substrate but much less so when acid-denatured haemoglobulin was used [ 3 ] . This result compares favourably with the present work, in which the optimum pH for protease activity of the Basidiobolus and Conidiobolus species was 5.5 when casein was used as substrate.…”
Section: Discussionmentioning
confidence: 99%
“…The dissolved protease obtained from each of the test isolates was purified further by chromatography using the modified methods of Somkuti & Babel [3] and Diamond & Denman [4]. Sephadex G-100 powder was allowed to swell in excess solvent (0.1 M sodium acetate buffer, pH 5.5) in a dark cupboard for 3 days.…”
Section: Second Stage Of Pun$cationmentioning
confidence: 99%